A national, prospective observational study of first recurrence after primary treatment for gynecological cancer in Norway. (24th September 2017) - Vistad, Ingvild; Bjørge, Line; Solheim, Olesya; Fiane, Bent; Sachse, Kurt; Tjugum, Jostein; Skrøppa, Siri; Bentzen, Anne G.; Stokstad, Trine; Iversen, Grete A.; Salvesen, Helga B.; Kristensen, Gunnar B.; et al.
Abstract: Introduction: Gynecological cancer patients are routinely followed up for five years after primary treatment. However, the value of such follow up has been debated, as retrospective studies indicate that first recurrence is often symptomatic and occurs within two to three years of primary treatment. We prospectively investigated time to first recurrence, symptoms at recurrence, diagnostic procedures, and recurrence treatment in gynecological cancer patients after primary curative treatment. Material and methods: Clinicians from 21 hospitals in Norway interviewed 680 patients with first recurrence of gynecological cancer (409 ovarian, 213 uterine, and 58 cervical cancer patients) between 2012 and 2016. A standardized questionnaire was used to collect information on self‐reported and clinical variables. Results: Within two years of primary treatment, 72% of ovarian, 64% of uterine, and 66% of cervical cancer patients were diagnosed with first recurrence, and 54, 67, and 72%, respectively, had symptomatic recurrence. Of symptomatic patients, 25–50% failed to make an appointment before their next scheduled follow‐up visit. Computer tomography was the most common diagnostic procedure (89% of ovarian, 76% of uterine, and 62% of cervical cancer patients), and recurrence treatment in terms of chemotherapy was most frequently planned (86% of ovarian, 46% of uterine, and 62% of cervical cancer patients). Conclusions: A majority of patients experienced symptomatic recurrence, but many patients failed to make an appointment earlier than scheduled. Most first recurrences occurred within two years of primary treatment; the mean annual incidence rate for years 3–5 after primary treatment was <7%. New models for follow up of gynecological cancer patients could be considered.